Adjuvant postoperative high-dose radiotherapy for atypical and malignant meningioma: A phase-II parallel non-randomized and observation study (EORTC 22042-26042). Issue 2 (August 2018) - Weber, Damien C.; Ares, Carmen; Villa, Salvador; Peerdeman, Saskia M.; Renard, Laurette; Baumert, Brigitta G.; Lucas, Anna; Veninga, Theo; Pica, Alessia; Jefferies, Sarah; Ricardi, Umberto; Miralbell, Raymond; et al.
Abstract: Purpose: The therapeutic strategy for non-benign meningiomas is controversial. The objective of this study was to prospectively investigate the impact of high dose radiation therapy (RT) on the progression-free survival (PFS) rate at 3 years in WHO grade II and III meningioma patients. Materials and methods: In this multi-cohorts non-randomized phase II and observational study, non-benign meningioma patients were treated according to their WHO grade and Simpson's grade. Patients with atypical meningioma (WHO grade II) and Simpson's grade 1–3 [Arm 1] entered the non-randomized phase II study designed to show a 3-year PFS > 70% (primary endpoint). All other patients entered the 3 observational cohorts: WHO grade II Simpson grade 4–5 [Arm 2] and Grade III Simpson grade 1–3 or 4–5 [Arm 3&4] in which few patients were expected. Results: Between 02/2008 and 06/2013, 78 patients were enrolled into the study. This report focuses on the 56 (median age, 54 years) eligible patients with WHO grade II Simpson's grade 1–3 meningioma who received RT (60 Gy). At a median follow up of 5.1 years, the estimated 3-year PFS is 88.7%, hence significantly greater than 70%. Eight (14.3%) treatment failures were observed. The 3-year overall survival was 98.2%. The rate of late signs and symptoms grade 3 or more was 14.3%. Conclusions: These data show that 3-year PFS for WHO grade II meningioma patients undergoing a complete resection (Simpson I–III) is superior to 70% when treated with high-dose (60 Gy) RT.